Determination of the optimal mating age of colonised Glossina brevipalpis and Glossina austeni using walk-in field cages in South Africa - Chantel J. de Beer; Gert J. Venter; Marc J. B. Vreysen (Parasites & Vectors, 2015)
Abstract Background For the control of Glossina brevipalpis and Glossina austeni that occur in South Africa an area-wide integrated pest management (AW-IPM) program with a sterile insect technique (SIT) component has been proposed. The quality of the released sterile male tsetse flies will greatly determine the success of the SIT component of the programme. Sterile males need to be able to compete with wild males immediately after their release in the affected area. The mating competitiveness can be affected by many factors including the optimal mating age of the fly which can have an impact on the timing of the release. Methods To assess the optimal mating age for G. brevipalpis and G. austeni, mating competitiveness studies were carried out in a walk-in field cage. First, the time of peak fly activity was determined by performing the experiment in the morning and then again in the afternoon. Thereafter, 3, 6 and 9-day-old male flies competed for 3-day-old virgin females. Results There were no significant differences in mating performance when the field cage experiments were done in the morning or in the afternoon. However, the mating latency was shorter in the afternoon than in the morning. For both species 9-day-old males mated significantly more often than 6 or 3-day-old males. Age did not affect the males’ ability to transfer sperm, mating duration or the mating latency. All females that mated were inseminated. Conclusions Age did influence the mating competitiveness of G. brevipalpis and G. austeni and it is recommended that sterile males are not released before the age of 9 days. Keeping the male flies in the rearing facility for 8 days will have economic and logistic consequences for AW-IPM programmes that have a SIT component.